2020
DOI: 10.1101/2020.04.03.021790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An oscillating MinD protein determines the cellular positioning of the motility machinery in archaea

Abstract: 1 these authors contributed equally MinD proteins are well studied in rod-shaped bacteria such as E. coli, where they display self-organized pole-to-pole oscillations that are important for correct positioning of the Z-ring at mid-cell for cell division. Archaea also encode proteins belonging to the MinD family, but their functions are unknown. MinD homologous proteins were found to be widespread in Euryarchaeota and form a sister group to the bacterial MinD family, distinct from the ParA and other related ATP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…A/D ATPases are also encoded in archaeal genomes (Leipe et al, 2002) , but little is known about their roles in subcellular organization. A recent study showed that archaeal species across several phyla, Euryarchaeota in particular, encode multiple A/D ATPases (Nußbaum et al, 2020) . Several of these species contained more than a dozen, including H. volcanii with 13 A/D ATPases, four of which are MinD-homologs.…”
Section: Discussionmentioning
confidence: 99%
“…A/D ATPases are also encoded in archaeal genomes (Leipe et al, 2002) , but little is known about their roles in subcellular organization. A recent study showed that archaeal species across several phyla, Euryarchaeota in particular, encode multiple A/D ATPases (Nußbaum et al, 2020) . Several of these species contained more than a dozen, including H. volcanii with 13 A/D ATPases, four of which are MinD-homologs.…”
Section: Discussionmentioning
confidence: 99%
“…A/D ATPases are also encoded in archaeal genomes 42 , but little is known about their roles in subcellular organization. A recent study showed that archaeal species across several phyla, Euryarchaeota in particular, encode multiple A/D ATPases 43 . Several of these species contained more than a dozen, including H. volcanii with 13 A/D ATPases, four of which are MinD-homologs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for spatial and temporal organization of Z-ring positioning in archaea is still unknown. Homologs of the MinD protein are present in H. volcanii but were recently shown not to be involved in Z-ring positioning, in contrast to the bacterial MinD protein (39). Our SepF depletion experiment showed that SepF had no negative effect on FtsZ1 ring formation as the number of additional FtsZ1 rings increased to up to five rings during late stages of depletion.…”
Section: Discussionmentioning
confidence: 99%